2003
DOI: 10.1161/01.cir.0000096485.64373.c5
|View full text |Cite
|
Sign up to set email alerts
|

Multilineage Potential of Cells From the Artery Wall

Abstract: Background-In diabetes or atherosclerosis, ectopic bone, fat, cartilage, and marrow often develop in arteries. However the mechanism is unknown. We have previously identified a subpopulation of vascular cells (calcifying vascular cells, CVC), derived by dilutional cloning of bovine aortic medial cells, and showed that they undergo osteoblastic differentiation and mineralization. We now show that CVC have the potential to differentiate along other mesenchymal lineages. Methods and Results-To determine the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
252
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(258 citation statements)
references
References 39 publications
4
252
1
1
Order By: Relevance
“…The term “perivascular cells” commonly includes classically defined pericytes surrounding the microvasculature, as well as other nonpericyte cells within the perivascular niche of the macrovasculature which have also been shown to display properties of MSCs 53, 54, 55. However, recent evidence would suggest a clear functional distinction between pericytes and MSC progenitors in the perivascular niche 56.…”
Section: Are Wharton's Jelly Mscs Perivascular In Origin?mentioning
confidence: 99%
“…The term “perivascular cells” commonly includes classically defined pericytes surrounding the microvasculature, as well as other nonpericyte cells within the perivascular niche of the macrovasculature which have also been shown to display properties of MSCs 53, 54, 55. However, recent evidence would suggest a clear functional distinction between pericytes and MSC progenitors in the perivascular niche 56.…”
Section: Are Wharton's Jelly Mscs Perivascular In Origin?mentioning
confidence: 99%
“…Studies have shown calcifying vascular cells to express pericyte markers, such as α‐smooth muscle actin and 3G5 93. These studies, in combination with the knowledge that pericytes can undergo chondrogenic, osteogenic, and adipogenic differentiation,107, 108 contrasts the function of vascular cells, which can only undergo chondrogenic and osteogenic differentiation 109. This prompted the hypothesis that calcifying vascular cells originate from pericytes that have been exposed to Wnt signaling 102…”
Section: Wnt Signaling In Pericytesmentioning
confidence: 99%
“…(1,(5)(6)(7)(8)(12)(13)(14)(15)(16)(17)(18) Our results are the first to relate DNA methylation with the loss of smooth muscle lineage marker SM22a in VSMCs incubated with high phosphate. SM22a promoter methylation decreases SM22a gene expression, and this fact could facilitate phenotypic transition of VSMCs to osteoblast-like cell.…”
Section: Discussionmentioning
confidence: 74%